Preparação de biocatalisadores por ativação interfacial de lipase microbiana em suporte hidrofóbico e aplicação na síntese de biolubrificante por reação de esterificação - Michelle Dias Alves (2016)
The aim of this study was the preparation and characterization of active biocatalysts prepared via interfacial activation of lipase from Thermomyces lanuginosus (TLL) on poly-(styrene-divinylbenzene) resin (PSty-DVB) to produce wax esters, an important class of compounds from the industrial point of view due to their lubricant properties,by esterification reaction. The influence of certain factors on the immobilization process such as pH, ionic strength, temperature, incubation time and initial protein loading varying from 10 to 200 mg/g of resin was evaluated. Under optimal experimental conditions (buffer sodium acetate 5 mM, pH 5.0, 25 °C, 15 h of incubation and initialprotein loading of 150 mg/g of resin), maximum immobilized protein concentration around 134 mg/g was observed. The immobilization of TLL on the support was also confirmed by attenuated total reflection Fourier transform infrared (ATRFTIR) and scanning electronic microscopy (SEM) analyses. The biocatalyst with the highest immobilized protein concentration was tested in the synthesis of cetyl linoleate, animportant unsaturated wax ester, in a solvent-free system in order to estimate its catalytic activity in esterification reaction. Maximum ester conversion around 90% for 30 min of reaction was observed. Moreover, immobilized TLL on PSty-DVB resin was more active in cetyl linoleate synthesis than Lipozyme TL-IM, a commercial biocatalyst. This biocatalyst was highly stable after five consecutive cycles of reaction.In a subsequent study, these prepared biocatalysts were also used to catalyze the synthesis of cetyl decanoate, a saturated wax ester with large industrial application. Here, the influence of some factors on the ester synthesis was succesfully examined in order to optimize the esterification reaction. A second-order reversible reaction kinetic model was proposed to estimate apparent kinetic constants and good agreement withexperimental data was observed (0.9430R20.9938). The reaction was a spontaneous and endothermic process. The biocatalyst prepared with initial protein loading of 115 mg/g of support (immobilized protein concentration of 108.7 ± 3.1 mg/g) yielded the highest value of initial reaction rate (113.5 mM/min of reaction) and chosen for furthertests. The reaction in heptane medium required a slight excess of cetyl alcohol (molar ratio acid:alcohol of 1:1.25) and 7.5% m/m of biocatalyst to attain a maximum conversion of 92.5% for 30 min of reaction. On the other hand, maximum conversion of 85.4% for the reaction performed in a solvent-free system was observed for 50 min of reaction conducted in an equimolar ratio acid:alcohol and 10% m/m of biocatalyst. Theproductivity for the reaction performed in heptane medium was 2.4 times higher than in a solvent-free system 68.5 and 28.2 mM/min.g of biocatalyst, respectively. The prepared biocatalyst more active than commercial biocatalysts such as IMMTLLT2 150 and Lipozyme TLIM that exhibited maximum conversion 92% for 45 and 75 min of reaction, respectively. The biocatalyst could be reused at least eight times without significant decrease of its activity.